Plant Extracts in the Bone Repair Process: A Systematic Review - Lyvia Lopes Miranda; Vanessa de Paula Guimarães-Lopes; Luciana Schulthais Altoé; Mariáurea Matias Sarandy; Fabiana Cristina Silveira Alves Melo; Rômulo Dias Novaes; Reggiani Vilela Gonçalves (Mediators of Inflammation)
Bone lesions are an important public health problem, with high socioeconomic costs. Bone tissue repair is coordinated by an inflammatory dynamic process mediated by osteoprogenitor cells of the periosteum and endosteum, responsible for the formation of a new bone matrix. Studies using antioxidant products from plants for bone lesion treatment have been growing worldwide. We developed a systematic review to compile the results of works with animal models investigating the anti-inflammatory activity of plant extracts in the treatment of bone lesions and analyze the methodological quality of the studies on this subject. Studies were selected in the PubMed/MEDLINE, Scopus, and Web of Science databases according to the PRISMA statement. The research filters were constructed using three parameters: animal model, bone repair, and plant extracts. 31 full-text articles were recovered from 10 countries. Phytochemical prospecting was reported in 15 studies (48.39%). The most common secondary metabolites were flavonoids, cited in 32.26% studies (n=10). Essential criteria to in vivo animal studies were frequently underreported, suggesting publication bias. The animals treated with plant extracts presented positive results in the osteoblastic proliferation, and consequently, this treatment accelerated osteogenic differentiation and bone callus formation, as well as bone fracture repair. Possibly, these results are associated with antioxidant, regenerative, and anti-inflammatory power of the extracts. The absence or incomplete characterization of the animal models, treatment protocols, and phytochemical and toxicity analyses impairs the internal validity of the evidence, making it difficult to determine the effectiveness and safety of plant-derived products in bone repair.